Prototipe Lori Inspeksi Jalan Rel Akademi Perkeretaapian Indonesia Api-02 - atmaja, dadang sanjaya; Kurniawan, Moch Aziz (Politeknik Perkeretaapian Indonesia Madiun, 2020)
Inspection railway are a re-design of railway that have been made in the Indonesian Railway Polytechnic. Inspection lorry repairs are carried out on the wheels, chassis, drive and body.The new lorry wheels are made of structural iron to reduce the total weight from 148 kg to 119 kg. The size of the wheel conus is the difference between the outer and inner diameter of 30 mm to minimize wheel friction with rails in the curved region. The chassis uses the ledder frame model with emphasis on the strength of 44.29 MPa and 0.095 MPa deflection to get optimal and reliable results on the 1067 track. The material uses galvanized hollow type iron weighing 125 kg. The environmentally friendly drive used in the railway inspection is an BLDC electric motor (brushless direct current) with a capacity of 2000 watts of power, a current of 35A and a rotational speed of 4250 Rpm. The railway inspection body is made of 3 layers fiber reinforced polymers of plastics (FRP) using a hand lay-up method that has a tensile stress value of 40.18 MPa and a strain value of 0.89%. The inspection body focuses on the aesthetics and ergonomics aspects in the form of a more attractive appearance, smoothness of design, passenger comfort and color harmony so that they have high selling.